BAT-TR: Turkish Adaptation of Burnout Assessment Tool (BAT) - Ömer Erdem Koçak; Oğuz Gençay; Wilmar B. Schaufeli (Psikoloji Çalışmaları)
Like many other European countries, Turkey has a high rate of employee burnout which negatively affects employees’ cognitive, emotional, and physiological functions. In this regard, accurate measurement of burnout and the development of interventions in Turkey are critical. It has been determined that the scale that has been used most frequently in the measurement of burnout has significant conceptual, technical, and application deficiencies. Thus, the Burnout Scale Consortium developed the Burnout Assesment Tool (BAT), with participants from 26 countries, to address these shortcomings. The purpose of this study is to adapt BAT to Turkish. Three studies were conducted for this purpose. First, the scale translation was completed, with the factorial structure being determined through a study of 295 participants. For the second study, the scale’s reliability and validity was tested with a study of 399 participants. For the third study, the scale’s nomological network validity was tested with a study of 2,778 participants, using the Job Demands-Resources Model (JD-R; Demerouti et al., 2001). As a result, the empirical evidence was found to support the six-factor structure, of which four are primary and two are secondary. Additionally, in line with the JD-R model (Demerouti et al., 2001), it was discovered that job demands positively predicted the scale, while job resources negatively predicted it. The BAT-TR was found to have a positive correlation with both the Maslach Burnout Inventory (MBI) and the Oldenburg Burnout Scale (OBS), but a negative correlation with work engagement. Additionally, it has been observed that, when compared to MBI and OBS, it has incremental validity for work-related attitudes and behaviors. Thus, the BAT-TR four core factors and two secondary symptoms provide strong evidence for the validity and reliability of the Turkish form. A discussion is presented with contributions to the literature and the study’s limitations, suggesting that the BAT-TR scale can be used in burnout research in Turkey.